2008
DOI: 10.1073/pnas.0803012105
|View full text |Cite
|
Sign up to set email alerts
|

Complexins facilitate neurotransmitter release at excitatory and inhibitory synapses in mammalian central nervous system

Abstract: Complexins (Cplxs) are key regulators of synaptic exocytosis, but whether they act as facilitators or inhibitors is currently being disputed controversially. We show that genetic deletion of all Cplxs expressed in the mouse brain causes a reduction in Ca 2؉ -triggered and spontaneous neurotransmitter release at both excitatory and inhibitory synapses. Our results demonstrate that at mammalian central nervous system synapses, Cplxs facilitate neurotransmitter release and do not simply act as inhibitory clamps o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 34 publications
14
158
1
1
Order By: Relevance
“…This agrees with previous observations, showing that insertions of 12 or 24 aa between the SNARE domain and the TMD abolishes SybII's ability to support vesicle priming (Deák et al, 2006). Yet, it contrasts with observations for null mutants of Complexin or Synaptotagmin at hippocampal synapses, indicating that linker mutations do not interfere with binding of these proteins to the SNARE complex (Geppert et al, 1994;Xue et al, 2008). Since linker extensions do not perturb SNARE complex assembly (McNew et al, 1999;Deák et al, 2006), it is likely that efficient priming of synaptic vesicles demands, beside trans-SNARE complex formation, a tight molecular link between the SNARE domain and the TMD.…”
Section: Linkers Impair Priming and Stimulus Secretion Coupling Of Ssvscontrasting
confidence: 41%
“…This agrees with previous observations, showing that insertions of 12 or 24 aa between the SNARE domain and the TMD abolishes SybII's ability to support vesicle priming (Deák et al, 2006). Yet, it contrasts with observations for null mutants of Complexin or Synaptotagmin at hippocampal synapses, indicating that linker mutations do not interfere with binding of these proteins to the SNARE complex (Geppert et al, 1994;Xue et al, 2008). Since linker extensions do not perturb SNARE complex assembly (McNew et al, 1999;Deák et al, 2006), it is likely that efficient priming of synaptic vesicles demands, beside trans-SNARE complex formation, a tight molecular link between the SNARE domain and the TMD.…”
Section: Linkers Impair Priming and Stimulus Secretion Coupling Of Ssvscontrasting
confidence: 41%
“…The activating function of complexin is conserved across all species (mammals, Drosophila, and C. elegans) and different types of Ca 2+ -triggered synaptic vesicle fusion studied to date (7,12,16,28,(34)(35)(36)(37)(51)(52)(53). Regulation of spontaneous release by complexin is less conserved among species and varies depending on experimental conditions: for example, in Drosophila spontaneous release increases with knockout of complexin (14,54).…”
Section: Discussionmentioning
confidence: 99%
“…Cplx3 expression in mouse brain is very low and does not contribute significantly to synaptic transmission in the brain regions tested so far (Xue et al, 2008). All four complexin isoforms are expressed in the retina, where Cplx1 and Cplx2 are found in conventional synapses of amacrine cells, whereas Cplx3 and Cplx4 are predominantly expressed in ribbon synapses of photoreceptors and bipolar cells (Reim et al, 2005).…”
Section: +mentioning
confidence: 96%
“…1C) (Reim et al, 2005). As we described previously, deletion of the Cplx3 gene leads to complete loss of Cplx3 protein in brain (Xue et al, 2008). Western blot analyses using extracts from adult retinae showed that expression of Cplx3 is abolished in homozygous Cplx3 knockouts (Fig.…”
Section: Generation Of Cplx4 Single-knockout Andmentioning
confidence: 96%
See 1 more Smart Citation